Outer Membrane Vesicles From Brucella melitensis Modulate Immune Response and Induce Cytoskeleton Rearrangement in Peripheral Blood Mononuclear Cells - Avila-Calderón, Eric Daniel; Medina-Chávez, Olín; Flores-Romo, Leopoldo; Hernández-Hernández, José Manuel; Donis-Maturano, Luis; López-Merino, Ahidé; Arellano-Reynoso, Beatriz; Aguilera-Arreola, Ma. Guadalupe; Ruiz, Enrico A.; Gomez-Lunar, Zulema; Witonsky, Sharon; Contreras-Rodríguez, Araceli (Frontiers in Microbiology, 2020)
Similar to what has been described in other Gram-negative bacteria, B. melitensis releases outer membrane vesicles (OMVs). OMVs from B. melitensis 16M and the rough-mutant B. melitensis VTRM1 were able to induce a protective immune response in mice. Some proteins which had previously been reported to induce protection against Brucella were found in the proteome of OMVs from B. melitensis 16M. However, the proteome of OMVs from B. melitensis VTRM1 had not previously been determined. In order to be better understand the role of OMVs in host-cell interactions, the aim of this work was to compare the proteomes of OMVs from B. melitensis 16M and the derived rough-mutant B. melitensis VTRM1, as well as to characterize the immune response induced by vesicles on host cells. Additionally, the effect of SDS and proteinase K on the stability of OMVs was analyzed. OMVs from B. melitensis 16M and the B. melitensis VTRM1 rough mutant were analyzed through liquid chromatography-mass spectrometry. OMVs were treated with proteinase K, sodium deoxycholate, and SDS, and then their protein profile was determined using SDS-PAGE. PBMCs were treated with OMVs in order to measure their effect on cytoskeleton, surface molecules, apoptosis, DNA damage, proliferation, and cytokine-induction. A total of 131 proteins were identified in OMVs from B. melitensis16M, and 43 in OMVs from B. melitensis VTRM1. Proteome comparison showed that 22 orthologous proteins were common in vesicles from both strains, and their core proteome contained Omp31, Omp25, GroL, and Omp16. After a subsequent detergent and enzyme treatment, OMVs from B. melitensis VTRM1 exhibited higher sensitive compared to OMVs from the B. melitensis 16M strain. Neither OMVs induced IL-17, proliferation, apoptosis or DNA damage. Nonetheless, OMVs from the smooth and rough strains induced overproduction of TNFα and IL-6, as well as actin and tubulin rearrangements in the cytoskeleton. Moreover, OMVs from both strains inhibited PD-L1 expression in T-cells. These data revealed significant differences in OMVs derived from the rough and smooth Brucella strains, among which, the presence or absence of complete LPS appeared to be crucial to protect proteins contained within vesicles and to drive the immune response.